2020
DOI: 10.1002/adma.202070061
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels: Mechanochemical Adhesion and Plasticity in Multifiber Hydrogel Networks (Adv. Mater. 8/2020)

Abstract: In article number 1905719, Jason A. Burdick and co‐workers describe the development of adhesive fibrous hydrogel networks where force induces chemical bonding between mixed fiber populations containing complementary chemical groups. This mechanochemical behavior can be applied to numerous material systems to introduce unique properties, from textiles to biomedical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…[44] This functional OHA with active carbonyl groups can create acidic-labile hydrazone bonds or imide bonds with therapeutic agents or other polymers through Schiff-base reaction under a mild condition. [45,46] Grafted antibodies or enzymes can preserve their biological activities. Notably, it has been demonstrated that OHA performs the potentials to construct injectable hydrogel.…”
Section: Oxidized Ha (Oha)mentioning
confidence: 99%
“…[44] This functional OHA with active carbonyl groups can create acidic-labile hydrazone bonds or imide bonds with therapeutic agents or other polymers through Schiff-base reaction under a mild condition. [45,46] Grafted antibodies or enzymes can preserve their biological activities. Notably, it has been demonstrated that OHA performs the potentials to construct injectable hydrogel.…”
Section: Oxidized Ha (Oha)mentioning
confidence: 99%
“…Highly functionalized monomers, such as methacrylated gelatin (GelMA), functionalized hyaluronic acid, and alginate have been used to fabricate hydrogel nanofibers without extra crosslinker. [ 58–62 ] Nanofibers composed of methacrylated poly(vinyl alcohol) and malleated hyaluronate could form crosslinking under UV to form nanofibrous hydrogels with high water contents. By simultaneous electrospinning and photo‐polymerization, double network agarose/PAAm nanofiber hydrogels were fabricated, resulting in the enhancement of strength and thermal stability.…”
Section: Conductive Electrospun Nanofibersmentioning
confidence: 99%
“…In 2020, an interesting combination of reactive chemistries has been proposed by integrating reactive units within func-tional block copolymers for in situ UV ES as well as complementarily reactive groups for covalent cross-linking. 205 Two separate solutions of HA modified with norbornenes exclusively functionalized with hydrazides and aldehydes were oppositely spun at the same time on a rotating mandrel (Fig. 11c).…”
Section: Reactive Electrospinning Designsmentioning
confidence: 99%
“…255 A new concept in the field of reactive ES for tissue engineering has been proposed by Davidson et al, where fiber-to-fiber cross-linking could be triggered by mechanical loading, therewith mimicking the force-responsive properties of the extra-cellular matrix. 205 To achieve this novel mechano-sensitive hydrogel, they have utilized hyaluronic acid as a functional polymer for the selective attachment of aldehyde or hydrazide units. Aldehyde functionalities in polysaccharides can be easily obtained by oxidizing the glucoside ring with sodium periodate as previously discussed (see section 4.2.1), whereas hydrazine moieties were introduced by reacting to the carboxylic groups in hyaluronic acid with adipic dihydrazide.…”
Section: In Situ Photo-induced Cross-linkingmentioning
confidence: 99%